Students' experiences of human-centred interventions in a design education setting - Chmela-Jones, K.A. (South African Journal of Higher Education, 2020)
International and national developments in graphic design practice have incorporated unprecedented levels of engagement with end-user clients and audiences. However, instructional graphic design courses for undergraduates have not kept pace with this trend or with associated professional practice expectations. Traditionally, graphic design practice relies on the ‘expert’, autocratic knowledge of the designer regarding the expected outcomes of the design brief. The use of co-operative tools and techniques such as human-centred design (HCD) enables the process to become a more democratic co-creation experience, where the client participants actively contribute to the development of the final design product. To prepare students for the new relationship between designers and end-users, newly developed HCD project interventions were created as part of the Communication Design modules offered in the third year Graphic Design Diploma programme at a University of Technology in South Africa. This paper reports on two human-centred interventions in different settings and involving different types of stakeholders, with a view to analysing the experiences of students as they conducted the projects to assess the viability of the HCD projects towards establishing a proposed new curriculum that incorporates aspects of HCD as a fundamental approach to graphic design practice.